Reinforcement of polymeric nanoassemblies for ultra-high drug loadings, modulation of stiffness and release kinetics, and sustained therapeutic efficacy. Issue 18 (2nd May 2018) - Ekladious, Iriny; Liu, Rong; Varongchayakul, Nitinun; Mejia Cruz, Luis A.; Todd, Daniel A.; Zhang, Heng; Oberlies, Nicholas H.; Padera, Robert F.; Colson, Yolonda L.; Grinstaff, Mark W.
Abstract : Beyond the MTD and LD50, use of novel ultra-high drug loaded nanoparticles. Abstract : The optimization of current polymeric nanoparticle therapies is restricted by low drug loadings and limited tunability of core properties. To overcome these shortcomings, a novel self-association approach is utilized to fabricate a dual-loaded poly(1, 2-glycerol carbonate)- graft -succinic acid-paclitaxel (PGC-PTX) conjugate nanoparticle (NP) in which the physical entrapment of free paclitaxel (PTX) affords unprecedented ultra-high drug loadings >100 wt%, modulation of mechanical stiffness, and tunable release kinetics. Despite high incorporation of free PTX (up to 50 wt%), the dual-loaded PGC-PTX nanocarriers ( i.e., PGC-PTX + PTX NPs) exhibit controlled and sustained drug release over 15 days, without burst release effects. Importantly, optimization of drug/material efficiency concomitantly affords improved in vitro efficacy. In vivo, PGC-PTX + PTX NPs are safely administered at doses exceeding the median lethal dose of standard PTX, while a single high dose significantly extends survival relative to weekly PTX administrations in a murine model of peritoneal carcinomatosis.